HUBUNGAN WAKTU PENYEMPROTAN PESTISIDA SEBELUM PANEN TERHADAP RESIDU PROFENOFOS DAN KARAKTERISTIK MUTU SAWI PAKCOY (Brassica rapa L) - Widnata Putra, I Made Prahadi; Harsojuwono, Bambang Admadi; Lani Triani, I.G.A (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 2 (2018): AprilDO - 10.24843/JRMA.2018.v06.i02.p07, 2018)
This research aims to 1) to know the correlation of different pesticide spraying time before harvest to the residual level of profenofos on the mustard pakcoy, 2) knowing the tendency of the relationship of different pesticide spraying time before harvest to the decrease of residual insecticidal content of  profenofos and the quality characteristic of the mustard pakcoy. This research uses regression and correlation analysis, the factors used are the last spraying time 0 days, 2 days, 4 days, 6 days, 8 days, 10 days, before harvest. Each treatment was group in to 3 to obtain 18 experimental units. The parameters observed were the residual insecticide content of profenofos, pakcoy mustard characteristics and the relationship between the use of pesticide with the time interval of spraying on the residual content and the characteristics of the pakcoy. The results showed that the time of spraying before harvest was related to the residue of profenofos on the mustard pakcoy with treatment 0, 2, 4, 6, 8, 10  days before harvest 0.001860 mg / kg, 0.000615 mg / kg, 0.000511 mg / kg, 0.000394 mg / kg, 0.000279 mg / kg, and 0.000270 mg / kg. quality evaluation results with yellowish green to green color criteria, freshness of light and slightly damaged 1.6 to 3.75 (very damaged-undamaged). The result of correlation between the use of pesticide with the time of spraying on the residual insecticide content of profenofos and the characteristics of the quality of pakcoy mustard with the correlation coefficient value of 0.80 to the residual content, 0.96 to the color, 0.88 to freshness, and 0.97 to the damage value.                                                                                                 Keywords:  Brassica rapa  L, time of pesticide spraying, profenofos and residue